Fear of COVID-19, loneliness, smartphone addiction, and mental wellbeing among the Turkish general population: a serial mediation model - Kayis, Ar; Satici, B.; Deniz, Me; Satici, Sa; Griffiths, Md (Informa UK Limited, 2021)
The novel coronavirus-2019 (COVID-19) pandemic has become a major health problem worldwide. The impact of COVID-19 has also been associated with psychological and social problems. The main objective of the present study was to examine the associations between fear of COVID-19 and mental wellbeing, through a serial mediation analysis that included loneliness and smartphone addiction. Utilising convenience sampling from 73 of 81 cities in Turkey via the web-based survey the present study comprised 773 participants (556 females and 217 males; aged between 18 and 66 years) were collected. Self-report data were collected including psychometric measures assessing fear of COVID-19, loneliness, smartphone addiction, and mental wellbeing. Fear of COVID-19 was found to have both a direct and indirect effect on mental wellbeing. In addition, results supported a serial mediation model where fear of COVID-19 was found to influence mental wellbeing via loneliness and smartphone addiction in a sequential manner. The findings suggest that higher fear of COVID-19 is associated with lower mental wellbeing by negatively affecting individuals’ emotion and behaviour.
Keywords: 3. Good health